Molecular Signatures of Human Regulatory T Cells in Colorectal Cancer and Polyps - Johdi, Nor Adzimah; Ait-Tahar, Kamel; Sagap, Ismail; Jamal, Rahman (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs), a subset of CD4+ or CD8+ T cells, play a pivotal role in regulating immune homeostasis. An increase in Tregs was reported in many tumors to be associated with immune suppression and evasion in cancer patients. Despite the importance of Tregs, the molecular signatures that contributed to their pathophysiological relevance remain poorly understood and controversial. In this study, we explored the gene expression profiles in Tregs derived from patients with colorectal cancer (CRC, n=15), colorectal polyps (P, n=15) and in healthy volunteers (N, n=15). Tregs were analyzed using CD4+CD25+CD127lowFoxP3+ antibody markers. Gene expression profiling analysis lead to the identification of 61 and 66 immune-related genes in Tregs derived from CRC and P patients, respectively but not in N-derived Treg samples. Of these, 30 genes were differentially expressed both in CRC- and P-derived Tregs when compared to N-derived Tregs. Most of the identified genes were involved in cytokine/chemokine mediators of inflammation, chemokine receptor, lymphocyte activation and T cell receptor (TCR) signaling pathways. This study highlights some of the molecular signatures that may affect Tregs expansion and possible suppression of function in cancer development. Our findings may provide a better understanding of the immunomodulatory nature of Tregs and could therefore open up new avenues in immunotherapy.